Tension-band wiring through a single cannulated screw combined with suture anchors to treat inferior pole fracture of the patella. Issue 4 (April 2023) - Liu, Chen-dong; Hu, Sun-jun; Chang, Shi-Min; Du, Shou-chao
Abstract: Purpose: To evaluate the feasibility and clinical outcomes of tension-band wiring through a single cannulated screw combined with two suture anchors in treating inferior pole fracture of the patella. Methods: Between September 2018 and September 2021, a total of 22 patients with a mean age of 55 years who sustained inferior pole fracture of the patella and were treated by tension-band wiring through a single cannulated screw combined with two suture anchors were enrolled. X-ray radiographs were performed to observe the bone union time. The duration of each operation was recorded to reflect the complexity of surgical treatment. Functional measurements, comprising range of motion (ROM), the Böstman scale, and the Knee Injury and Osteoarthritis Outcome Score (KOOS), were taken. Postoperative complications including fixation failure, incision infection, loss of reduction, and malunion were evaluated. Results: All patients were followed up for an average of 17 months (range: 12–25 months). The average clinical bone union time was 8 weeks (range: 6–12 weeks), and the radiographic bone union time was 11 weeks (range: 8–12 weeks). At the final follow-up, the mean ROM was 136° (range: 115°-140°), the KOOS was 85 (range: 68–100) and the Böstman score was 28 (range: 20–30); these outcomes were classified as excellent in 17 cases and good in 5 cases, with no instances of poor results. Loss of reduction occurred in one case, while no cases of incision infection, fixation failure or malunion were observed. Conclusion: For inferior pole fracture of the patella, tension-band wiring through a single cannulated screw combined with suture anchors can offer sufficient fixation stability to achieve a satisfactory clinical outcome with reduced operational complexity; this procedure should be recommended in clinical practice.